PENERAPAN MODEL INTEGRATIF SCRUM DENGAN UX DESIGN DALAM PENGEMBANGAN WEBSITE E-COMMERCE YANG EFISIEN DAN USER-CENTERED - Prastichia, Vistalia Putri; Priyanto, Adhi; Puryono, Daniel Alfa (LPPM Politeknik Saint Paul Sorong, 2025)
The rapid development of e-commerce demands a system that is not only functional but also provides an optimal user experience. This research aims to apply an integrative model between SCRUM and UX Design methods in the process of developing EXO Thrifting Pati's e-commerce website. The approach method used in this research is DSRM, which includes the stages of problem identification, model design, implementation, and evaluation. The results of this study show that the integration between SCRUM and UX Design can improve the efficiency of the development process and the quality of user experience. Usability test results produce a very good level of user satisfaction, with an interface that is easy to use, attractive, and according to user needs. This integrative model was effective and can be a reference for the development of other user-oriented digital systems.